Immune function and the swimmer: twenty-five years of enquiry at the AIS - Fricker, P. (XIIth International Symposium for Biomechanics and Medicine in Swimming, 2014)
So what have we concluded? Training is associated with dose responsive and cumulative immunosuppression. The risk of upper respiratory illness may be linked to changes in immune status. Not all upper respiratory symptoms are infectious in origin. Mild illness can affect performance adversely in high performance athletes. There are genetic markers which may indicate risk of infection. Interventions such as anti-viral agents have not proved effective. Interventions with probiotics show promise in enhancing immune status